Secure Digital Asset Repository - Mohd Mahpos, Nazurah Husna (Universiti Teknologi PETRONAS, 2011)
As the industry evolves into technology driven businesses, an increasing number of companies are reaching a critical pain in needing to control and manage their vast amounts of digital media assets. Technically speaking, a digital asset is any form of media that has been turned into a binary source. Digital assets, which for textile mills include everything from artwork, logos, photos, text documents and even email, are proving to be valuable assets in terms of both productivity and company valuation. Many organizations thought that secure digital asset repository as part of their business-critical strategy for managing and sharing digital assets. They need dedicated solution to help overcome operational and organisational challenges unique to them. Secure digital asset repository allows company to create a custombranded, password-protected area where company can exchange business files with clients easily, securely, and professionally. Whether company deal with files that are simply too large to transfer by email, need secure file transfer or just need a certain data being revealed, secure digital asset repository can provide a solution. This paper focuses several features in the secure digital asset repository application.